BEYOND THE DATA: CONTINUOUS GLUCOSE MONITORING (CGM) TECHNOLOGIES, HEALTH EQUITY, AND THE DIGITAL DIVIDE IN DIABETES MANAGEMENT. A NARRATIVE REVIEW - Aleksandra Banaś; Hubert Bigajski; Szymon Janczarski; Klaudia Kwolek; Wiktoria Laskowska; Maciej Michalik; Aleksandra Owczarska; Marcel Pilarek; Dominika Sarna; Piotr Widera (International Journal of Innovative Technologies in Social Science, 2025)
Continuous glucose monitoring (CGM) represents a paradigm shift in diabetes management, transitioning care from reactive monitoring to proactive glycemic control; however, its adoption remains stratified by deep-seated socioeconomic and structural, and technological inequities. This narrative review synthesizes literature published between 2017 and 2025 to evaluate the clinical efficacy of CGM while interrogating the socio-technical barriers shaping its accessibility. A thematic analysis of current evidence confirms that while CGM significantly improves HbA1c, quality of life, and hypoglycemia reduction across Type 1 and Type 2 diabetes, access to these outcomes is severely constrained by systemic and digital obstacles. Key findings identify a “coverage patchwork” wherein high out-of-pocket costs and administrative hurdles disproportionately restrict access for Medicaid beneficiaries and low-income populations. Furthermore, the review highlights persistent racial disparities driven by provider implicit bias, alongside a “digital divide” where limited connectivity and low eHealth literacy impede effective utilization. Consequently, without intervention, CGM risks functioning as an “accelerator of disparities,” creating a two-tier healthcare system that privileges “data-rich” early adopters while leaving marginalized groups behind. The authors conclude that bridging this gap requires a multifaceted strategy integrating policy reform, inclusive device design, and literacy-centered education to ensure technological innovation advances health equity rather than reinforcing the “Matthew Effect” in diabetes management.